Gender differences in virtual collaboration on a creative design task - SCHILLER, Shu (Institutional Knowledge at Singapore Management University, 2011)
Collaboration is an important activity in every organization because it fundamentally affects work processes and organizational outcomes. Diversity adds complexity to the mechanism of virtual teams because teams routinely operate virtually by spanning temporal, geographic, national, and cultural boundaries. One important way to decode such complexity is to understand gender differences and their impacts on virtual modes of collaboration. In this research, we examine gender differences and how they influence outcomes and attitudes on virtual collaboration in the context of team gender composition. Phase one of our study involved male-male dyads and female-female dyads that collaborated virtually in Second Life. The preliminary results show that impression management and team effort both have significant positive impacts on team outcomes (trust and satisfaction). Phase two of our study is on dyads of mixed gender.